Coorperation between Indonesia and Cambodia in Combating Human Trafficking - M. Auri, saskiya_prambandari; Bambang W. Nugroho (Andalas Institute of International Studies, 2025)
Human trafficking (TPPO) against Indonesia citizens (WNI) in Cambodia has increased significantly between 2021 and 2023. One of the main factors driving this high number of cases is the prevalence of job vacancy scams targeting Indonesian job seekers with the lure of high salaries and atrractive working conditions. This study analyzes the implementation of bilateral coorperation between Indonesia and Cambodia in handling TPPO through three key aspects: intelligence exchange, lawa enforcement capacity building, and retriation mechanisms. The method used is a qualitative approach through document analysis, including the 2022 Memorandum of Understanding (MoU), ASEAN-ACT reports, and IOM data. The results of the study show that despite improved coordination and success in several cases, disparities in law enforcement capacity between countries remain a major obstacle. Recommendations include policy harmonization, joint training, and strengthening multistakeholder coordination mechanisms to maximize the effectiviness of bilateral cooperation.